Pengembangan Aplikasi Perangkat Bergerak Jadwal Olahraga Outdoor berdasarkan Waktu dan Kondisi Cuaca menggunakan Metode Location Based Service, Dark Sky API dan Android Alarm Manager - Alva Yonara Puramandya; Agi Putra Kharisma; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Outdoor exercise is exercise that is done outdoors. Outdoor exercise is very good for mind and body. The problem that often occurs when it comes to exercising outdoor is bad weather. In addition, we need to pay attention to the right time because the ray of the sun does not always nourish the body. As a result of these problems make people lazy to exercise. Based on this problem, researcher had developed a mobile application that can provide outdoor exercise schedule to the user. Application was developed by using Waterfall method which is one of the approaches to Software Development Lifecycle (SDLC). In this application Location Based Service (LBS), Dark Sky API, and Android Alarm Manager are implemented. In system testing, researcher used black box and usability testing. The result of black box testing is 100% valid. System Usability Scale (SUS) method was used in Usability Testing which obtained a score of 77. From the result of the score, the application is in the category of acceptability Acceptable, grade C, and adjective rating Good.